1999
DOI: 10.1677/joe.0.1610413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH, prolactin and cortisol on hepatic heat shock protein 70 expression in a marine teleost Sparus sarba

Abstract: Heat shock protein 70 (HSP70) expression was assessed in hepatic tissue of a marine teleost Sparus sarba after exogenous hormone administration. Using a PCR-amplified, homologous HSP70 cDNA clone, as a probe in Northern analysis, we detected a 2·3 kb transcript which was elevated after exposure to a temperature 7 C above the ambient. For our studies on hormonal effects on HSP70 expression, groups of fish were administered recombinant bream GH (rbGH), ovine prolactin (oPRL) or cortisol daily over a 7-day period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
4
34
1
2
Order By: Relevance
“…The cell line is relatively easy to maintain as we have deduced the optimum FBS requirement and growth temperature. Over the past few years we have been studying the effects of hormones on hsp70 expression in vivo (Deane et al 1999(Deane et al , 2000 but due to endocrine axis overlap and crosstalk, firm conclusions about hormone specific effects on hsp70 expression await the application of suitable in vitro models. The development of the cell line in the present study may prove to be useful towards these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The cell line is relatively easy to maintain as we have deduced the optimum FBS requirement and growth temperature. Over the past few years we have been studying the effects of hormones on hsp70 expression in vivo (Deane et al 1999(Deane et al , 2000 but due to endocrine axis overlap and crosstalk, firm conclusions about hormone specific effects on hsp70 expression await the application of suitable in vitro models. The development of the cell line in the present study may prove to be useful towards these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular stress response to low environmental O 2 levels is variable in fish, and high levels of tissue, cell and temporal specificity in terms of the levels of HSP expression have been reported (Airaksinen and Nikinmaa, 1995;Currie and Tufts, 1997;Currie and Boutilier, 2001;Currie et al, 2010). Furthermore, a decrease in HSP70 mRNA production in hepatic tissue of sparids (family Sparidae) has been reported after exogenous administration of growth hormone (Deane et al, 1999). Despite this body of research, we know very little regarding the effects of ploidy and/or transgenesis on the cellular stress response in fish.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest study to imply possible involvement of GH and PRL on fish HSP expression was performed using exogenous administration of recombinant bream GH or ovine prolactin to silver sea bream (Deane et al 1999). In this study it was found that both hormones reduced hepatic HSP70 mRNA and protein amounts in comparison with saline-treated controls.…”
Section: Introductionmentioning
confidence: 82%
“…However, much less is known about the effect of hormones on the regulation and expression of HSPs and most studies that have investigated hormone effects on fish HSP expression have used cortisol. For example silver sea bream (Sparus sarba), that were administered intraperitoneal injections of cortisol did not have any changes in hepatic HSP70 levels (Deane et al 1999). Subsequently, studies on rainbow trout (Oncorhynchus mykiss) and tilapia (Oreochromis mossambicus) also demonstrated that elevated cortisol per se did not alter basal HSP70 levels in hepatic or gill tissues (Basu et al 2001(Basu et al , 2002b.…”
Section: Introductionmentioning
confidence: 99%